2018
DOI: 10.1101/287466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early identity recognition of familiar faces is not dependent on holistic processing

Abstract: Highlights• Holistic processing is not necessary for early identity recognition of familiar faces.• Inverted faces and isolated features can effectively activate the perceptual memory of a familiar face.• This effectiveness was observed for eyes, but not mouths. AbstractIt is widely accepted that holistic processing is critical for early face recognition, but recent work has suggested a larger role for feature-based processing. The earliest step in familiar face recognition is thought to be matching a perceptu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 70 publications
3
8
0
Order By: Relevance
“…In an a priori power analysis applying G*Power 3.1 (Faul et al., 2009), we assumed the standard significance criteria (α = .05 two-tailed, 1-β = .80), a small-to-medium effect size ( f = .23) with a repeated-measures analysis of variance (ANOVA), and found a required minimum sample size of 15 participants. Previous investigations concerning the repetition priming of human faces included 17-24 participants (Feuerriegel, Keage, et al., 2018; Mohr et al., 2018; Nie, Li, et al., 2016; Nie, Ye, et al., 2016; Wiese et al., 2017). Thus, we believed the current sample size of 22 to be satisfactory.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In an a priori power analysis applying G*Power 3.1 (Faul et al., 2009), we assumed the standard significance criteria (α = .05 two-tailed, 1-β = .80), a small-to-medium effect size ( f = .23) with a repeated-measures analysis of variance (ANOVA), and found a required minimum sample size of 15 participants. Previous investigations concerning the repetition priming of human faces included 17-24 participants (Feuerriegel, Keage, et al., 2018; Mohr et al., 2018; Nie, Li, et al., 2016; Nie, Ye, et al., 2016; Wiese et al., 2017). Thus, we believed the current sample size of 22 to be satisfactory.…”
Section: Methodsmentioning
confidence: 99%
“…There were equal numbers of male and female faces. We selected celebrities’ facial images as stimuli because previous studies found that such faces elicited stronger N250r and N400 activations than did unfamiliar faces (Engst et al., 2006; Herzmann, 2016; Mohr et al., 2018; Nie, Li, et al., 2016; Nie, Ye, et al., 2016; Schweinberger & Neumann, 2016; Wiese et al., 2013). Similar to previous investigations (Nie, Li, et al., 2016; Nie, Michael, et al., 2014; Nie, Ye, et al., 2016), all the current images were processed into standardized colored faces against white backgrounds using Adobe Photoshop CC 2017.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations